Environmental and economic impacts of soil erosion and fertility mining in northern Tanzania - Nkonya, Ephraim M.; Barkley, Andrew P.; Hamilton, Stephen F.; Bernardo, Daniel J. (Agricultural and Applied Economics Association, 1999)
This paper develops a soil conservation model that is relevant to smallholder farmers who apply little or no fertilizer. Empirical results drawn from northern Tanzania imply that, ignoring fertility mining problem in model specification leads to overestimation of profits for farms that apply little or no fertilizer. The model also shows that, the impact of output price on soil conservation efforts depends on the curvature of the soil erosion function.